Adolescent Conformity Assessed from the Residence: Comparative Research on Student Conformity of Two Muhammadiyah Junior High Schools - Septiana Rahayuningrum; Ratna Sari (International Journal of Islamic Educational Psychology, 2021)
This study aims to determine the conformity of adolescents in SMP Muhammadiyah 2 Galur and SMP Muhammadiyah Al Manar Boarding School and to analyze the differences there. This research is survey research using a quantitative approach with a comparative study method. The population in this study was 171 students, while the sample size was 120 students. The data analysis technique used the Mann Withney test to see the results of differences in adolescent conformity. The final results of this study indicated that (1) the level of conformity of the students of SMP Muhammadiyah 2 Galur was medium; (2) the conformity level of the students of SMP Muhammadiyah Al Manar Boarding School was medium and high; (3) there was no significant difference regarding the level of adolescent conformity between students of SMP Muhammadiyah 2 Galur and students of SMP Muhammadiyah Al Manar Boarding School as evidenced by the results of the Mann Withney test with the Sig. 0.129 0.05.